1970
DOI: 10.1021/j100699a042
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nuclear magnetic resonance spectroscopy. Solvent effects on chemical shifts

Abstract: The 13C chemical shift of chloroform has been measured in a variety of solvents. Relative to dilute solution in cyclohexane, all of the solvents studied resulted in downfield shifts which, with the exceptions of benzene and acetonitrile, correlate linearly (r = 0.982) with the changes in proton shifts in the same solvents. The results, taken with the variation of the 18C-H coupling constant with solvent, suggest that the solvent effects arise from changes in the average distance of the bonding electrons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

1972
1972
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 3 publications
1
19
0
3
Order By: Relevance
“…The sensitivity of the chemical-shift displacement due to a slight variation of electron distribution is significantly enhanced by a contribution of the paramagnetic current around the heteroatom under consideration. Therefore, if adequate accuracy of the chemicalof data using this method have been accumulated (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the chemical-shift displacement due to a slight variation of electron distribution is significantly enhanced by a contribution of the paramagnetic current around the heteroatom under consideration. Therefore, if adequate accuracy of the chemicalof data using this method have been accumulated (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The next 'specific' interactions can probably be best described in terms of weak hydrogen bonding between the acid anion and the alkyl hydrogen atoms in the tetraalkylaminoniu~~~ ions. Hydrogen bonding to C-H bonds is known to cause low-field shifts for both 13C and lH nuclei (17). The net changes in the external shielding factors can be therefore represented for the aqueous solutions of an acid AH as:…”
Section: Resultsmentioning
confidence: 99%
“…Although the pmr chemical shifts differences are smaller in magnitude, and therefore less reliable, the observed trends can again be interpreted in terms of the hydrogen bonding to the medium and they support conclusions drawn from the results obtained for the carbon chemical shift data. Figure 3 shows model of specific acid anion hydrogen bonding since it has been shown that 13C chemical shifts in CHC13 are almost exactly two times as sensitive to hydrogen bonding interactions as the corresponding 'H chemical shifts (17).…”
Section: Resultsmentioning
confidence: 99%
“…(18). Although Roberts has suggested (20) that anisotropy effects may be negligible at the carbon nucleus of the solute, there is ample evidence of appreciable ring current effects on carbon chemical shifts (21 atoms may well be of this origin, with the small difference in relative shielding reflecting the asymmetric orientation of the solvent molecules necessitated by lone pair repulsions of the oximino oxygen.…”
Section: Methodsmentioning
confidence: 99%